A systematic review of potential long-term effects of sport-related concussion. Issue 12 (28th April 2017) - Manley, Geoff; Gardner, Andrew J; Schneider, Kathryn J; Guskiewicz, Kevin M; Bailes, Julian; Cantu, Robert C; Castellani, Rudolph J; Turner, Michael; Jordan, Barry D; Randolph, Christopher; Dvořák, Jiří; Hayden, K. Alix; et al.
Abstract : Objective: Systematic review of possible long-term effects of sports-related concussion in retired athletes. Data sources: Ten electronic databases. Study selection: Original research; incidence, risk factors or causation related to long-term mental health or neurological problems; individuals who have suffered a concussion; retired athletes as the subjects and possible long-term sequelae defined as > 10 years after the injury. Data extraction: Study population, exposure/outcome measures, clinical data, neurological examination findings, cognitive assessment, neuroimaging findings and neuropathology results. Risk of bias and level of evidence were evaluated by two authors. Results: Following review of 3819 studies, 47 met inclusion criteria. Some former athletes have depression and cognitive deficits later in life, and there is an association between these deficits and multiple prior concussions. Former athletes are not at increased risk for death by suicide (two studies). Former high school American football players do not appear to be at increased risk for later life neurodegenerative diseases (two studies). Some retired professional American football players may be at increased risk for diminishment in cognitive functioning or mild cognitive impairment (several studies), and neurodegenerative diseases (one study). Neuroimaging studies show modest evidence of macrostructural, microstructural, functional and neurochemical changes in some athletes. Conclusion: Multiple concussions appear to be a risk factor for cognitive impairment and mental health problems in some individuals. More research is needed to better understand the prevalence of chronic traumatic encephalopathy and other neurological conditions and diseases, and the extent to which they are related to concussions and/or repetitive neurotrauma sustained in sports.